Psychosocial work characteristics and anxiety and depressive disorders in midlife: the effects of prior psychological distress. Issue 9 (3rd April 2008) - Stansfeld, S A; Clark, C; Caldwell, T; Rodgers, B; Power, C
Abstract : Objectives: The association between work stressors and adult psychiatric diagnoses may be biased by prior psychological distress influencing perception of work or selection into unfavourable work. This study examines the extent to which the association between work stressors and adult psychiatric diagnoses is explained by associations with earlier psychological distress and whether childhood and early adulthood psychological distress influences reported midlife work characteristics. Methods: Follow-up at 45 years of age of 8243 participants in paid employment from the 1958 British Birth Cohort. Karasek's work characteristics and psychiatric diagnoses (Revised Clinical Interview Schedule) were measured at 45 years. Childhood internalising and externalising problems were measured at 7, 11 and 16 and malaise at 23 and 33 years. Results: Internalising behaviours in childhood and early adult psychological distress predicted adverse work characteristics in mid-adulthood. High job demands (women: relative risk (RR) = 1.75, 95% CI 1.2 to 2.5; men: RR = 4.99, 95% CI 2.5 to 10.1), low decision latitude (RR = 1.46, 95% CI 1.1 to 1.9), high job strain (OR = 1.88, 95% CI 1.5 to 2.4), low work social support (RR = 1.97, 95% CI 1.5 to 2.6) and high job insecurity (OR = 1.86, 95% CI 1.4 to 2.4) were associated with mid-adulthood diagnoses. The association between work stressors and mid-adulthood diagnoses remained after adjustment for internalising behaviours and malaise at 23 and 33 years although diminished slightly in magnitude (eg, adjusted RR for support = 1.82, 95% CI 1.4 to 2.4; job strain OR = 1.78, 95% CI 1.4 to 2.3). Conclusions: Childhood and early adulthood psychological distress predict work characteristics in mid-adulthood but do not explain the associations of work characteristics with depressive episode and generalised anxiety disorder in midlife. Work stressors are an important source of preventable psychiatric diagnoses in midlife. Psychological distress may influence selection into less advantaged occupations with poorer working conditions that may increase the risk of future depressive and anxiety disorders.